Job Satisfaction among Young Workers in Eastern and Southern Africa: A Comparative Analysis - Andy McKay; Andrew T. Newell; Cinzia Rienzo (Institute of Labor Economics (IZA), 2018)
The creation of job opportunities for the increasingly educated youth population is a major current policy challenge in sub-Saharan Africa, even though very little is known about the extent to which young workers in the region are satisfied with the employment they currently have. This paper aims to help to fill this latter gap by presenting an analysis of job satisfaction of youth aged 15-29 in four countries from Eastern and Southern Africa: Madagascar, Malawi, Uganda and Zambia. We estimate ordered probit models of the degree of satisfaction in a respondent's main job, using data from the School-to-work Transition Survey (SWTS). It turns out that while a majority of workers are satisfied with their work, a large minority are not. We find that being over-educated or under-educated for the current job is strongly and negatively correlated with job satisfaction in all four countries. With respect to employment status, we find that those who report having chosen to be self-employed are substantially most satisfied in all four countries compared to formal sector wage employees, after controlling for many other factors. Formal wage employees are more satisfied than informal employees in only two of the four countries. These results reinforce the case made by Fields (2014) for not assuming that all self-employment is a 'last resort'. They also raise questions about the quality of available wage jobs for young people.
Keywords: I31; J28; O55; 330; job satisfaction; young workers; Eastern and Southern Africa